Cry4Ba and Cyt1Aa proteins from Bacillus thuringiensis israelensis: Interactions and toxicity mechanism against Aedes aegypti. (15th September 2015) - Elleuch, Jihen; Jaoua, Samir; Darriet, Frédéric; Chandre, Fabrice; Tounsi, Slim; Zghal, Raida Zribi
Abstract: Individual crystal proteins from Bacillus thuringiensis israelensis exhibit variable levels of insecticidal activities against mosquito larvae. In all cases, they are much less active compared to the whole crystal proteins due to described complex synergistic interactions among them. In the present study we investigated the effects of Cyt1A98 (a Cyt1Aa type protein) on Cry4BLB (a Cry4Ba type toxin) insecticidal activity toward the dengue vector Aedes aegypti . The bioassay analyses demonstrated the ability of Cyt1A98 protein to enhance Cry4BLB toxin larvicidal activity even at a low proportion in the mixture (1%). In vitro interaction assays showed that Cyt1A98 provides supplementary binding sites for Cry4BLB in A. aegypti BBMVs. Moreover, it enhances the formation of Cry4BLB oligomeric structure. These results support that Cyt1A98 protein could act as a membrane-bound receptor fixing Cry4BLB δ-endotoxins and promoting its oligomerization. Graphical abstract: Highlights: The mixture of Cry4BLB and Cyt1A98 showed synergistic activity against Aedes aegypti larvae. Cyt1A98 improves Cry4BLB binding to A. aegypti BBMV. Cyt1A98 interact with Cry4BLB in membrane-bound state as well as in solution. Cyt1A98 proteins function as a membrane-bound receptor for Cry4BLB toxins. Cyt1A98 enhances the formation of Cry4BLB oligomeric structure.